Internet Connection Control based on Idle Time Using User Behavior Pattern Analysis - Hardiansyah, Fadilah Fahrul; Buliali, Joko Lianto; Wibisono, Waskitho (Politeknik Elektronika Negeri Surabaya (PENS), 2014)
The increase of smartphone ability is rapidly increasing the power consumption. Many methods have been proposed to reduce smartphone power consumption. Most of these methods use the internet connection control based on the availability of the battery power level regardless of when and where a waste of energy occurs. This paper proposes a new approach to control the internet connection based on idle time using user behavior pattern analysis. User behavior patterns are used to predict idle time duration. Internet connection control performed during idle time. During idle time internet connection periodically switched on and off by a certain time interval. This method effectively reduces a waste of energy. Control of the internet connection does not interfere the user because it is implemented on idle time.Keywords: Smartphone, User Behavior, Pattern Recognition, Idle Time, Internet Connection Control